Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Review: 62

Answer

$x_{1}=\dfrac{17 + \sqrt{145}}{9}$ and $x_{2}=\dfrac{17 - \sqrt{145}}{9}$

Work Step by Step

Given $(3x-4)^2=10x \longrightarrow (3x)^2 - 2(3x)(4) + 4^2 = 10x \longrightarrow \\ 9x^2 - 24x + 16 - 10x = 0 \longrightarrow 9x^2 - 34x + 16 = 0$ $a = 9, \ b = -34, \ c = 16$ Using the quadratic formula: $\dfrac{-b\pm \sqrt{b^2-4ac}}{2a} , $ we have: $\dfrac{-(-34) \pm \sqrt{(-34)^2-4\times 9\times 16}}{2\times 9} \longrightarrow \dfrac{34\pm \sqrt{1156-576}}{18} = \dfrac{34\pm \sqrt{580}}{18} = \dfrac{34\pm 2\sqrt{145}}{18} = \dfrac{17\pm \sqrt{145}}{9}$ Therefore, the solutions are $x_{1}=\dfrac{17 + \sqrt{145}}{9}$ and $x_{2}=\dfrac{17 - \sqrt{145}}{9}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.